2022
DOI: 10.6007/ijarbss/v12-i9/14727
|View full text |Cite
|
Sign up to set email alerts
|

Work-Life Balance and Employee Performance in Selected Manufacturing Company

Abstract: The purpose of this study is to examine the relationship between work-life balance (WLB) and employee performance. Specifically, based on Hayman's (2005) concept on WLB, the authors tested how four dimensions in WLB are correlated to employee performance. Furthermore, employee performance constructs were derived from the Individual Work Performance Questionnaire (IWPQ) developed by (Koopmans et al., 2013). Using a survey questionnaire, this research was conducted with sample of 132 employees from a selected ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…This was also confirmed by a significance t of 0.007 (in model 5) or less than 0.05 which indicates that the effect exerted by the work-life balance variable is significant on employee performance. The proof of the effect of work-life balance on employee performance in this study showed that there are results of study that are in line with various previous studies on similar topics, which stated that work-life balance has a significant and positive effect on employee performance in various industries (Shaari et al, 2022;Susanto et al, 2022;Melayansari & Bhinekawati, 2020;Ngozi & Chinelo, 2020;Victoria et al, 2019;Jackson & Fransman, 2018;Lazǎr et al, 2010).…”
Section: Work-life Balance Towards Employee Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…This was also confirmed by a significance t of 0.007 (in model 5) or less than 0.05 which indicates that the effect exerted by the work-life balance variable is significant on employee performance. The proof of the effect of work-life balance on employee performance in this study showed that there are results of study that are in line with various previous studies on similar topics, which stated that work-life balance has a significant and positive effect on employee performance in various industries (Shaari et al, 2022;Susanto et al, 2022;Melayansari & Bhinekawati, 2020;Ngozi & Chinelo, 2020;Victoria et al, 2019;Jackson & Fransman, 2018;Lazǎr et al, 2010).…”
Section: Work-life Balance Towards Employee Performancesupporting
confidence: 90%
“…And thus ultimately improving their health, making workers more productive at work, and resulting in fewer sick days and absences from work (Holden & Sunindijo, 2018). Even the implications of work-life balance on employee productivity or performance have also been proven in various studies which confirm that work-life balance significantly and positively affects employee performance (Shaari et al, 2022;Susanto et al, 2022;Melayansari & Bhinekawati, 2020;Ngozi & Chinelo, 2020;Victoria et al, 2019;Jackson & Fransman, 2018;Lazǎr et al, 2010). This positive influence means that with better or healthier work-life balance conditions felt by employees, in the end it will also increase the performance or productivity of employees, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers had defined the life harmony and work-life balance as the appropriate separation of time and focus between work and family (Adikaram and Jayatilake 2016). For example, association between work-life balance and gender differences was noticed within the manufacturing sector in Mumbai, India (Kshirsagar 2015). Moreover, positive relationship between life harmony and employee productivity was noticed in Pakistani banking sector (Ansari et al 2015).…”
Section: Life Harmonymentioning
confidence: 99%